Prospek Masa Depan Hukum Islam di Indonesia - Mohammad Sandia (JURNAL ALAMIAH, 2021)
It is a fact that the majority of Indonesia's population is Muslim, therefore it becomes a necessity when Islam has a strategic role for the legal system in Indonesia. However, the fact is that the opposite is true, the current legal system only adopts very few Islamic law. The developments in the last two decades have actually shown the emergence of an Islamophobic movement which considers Islamic law to be a primitive law with conditions of violence.As a state based on law with the philosophy of Pancasila, the state protects religion, adherents of religion, and even tries to include religious law and Islamic religious law in the life of the nation and state. As stated by the founding father of the Republic of Indonesia, Mohammad Hatta, that in the regulation of the legal state of the Republic of Indonesia, Islamic Shari'a based on the Qur'an and Hadith can be used as Indonesian laws and regulations so that Muslims have a Shari'ah system that is in accordance with Indonesian conditions. .The development of Islamic law in Indonesia and society in general, has a bright opportunity in the development of national law, because socio-anthropologically and emotionally, Islamic law is very close to society, the majority of which is Muslim, besides historically Islamic law has been known long before the existence of the legal system. Others in Indonesian society. Future opportunities for Islamic law in Indonesia are increasingly open, because many rules in Islamic law have been ratified into national law, this shows how the political will of the government has provided a great response and opportunities for Islamic law. In the future, the role of ulama, ustaz, preachers, academics with constructive development and research can support the development of Islamic law in Indonesia.